Accelerated long-term forgetting in resected and seizure-free temporal lobe epilepsy patients. (January 2019) - Visser, M.; Forn, C.; Gómez-Ibáñez, A.; Rosell-Negre, P.; Villanueva, V.; Ávila, C.
Abstract: Episodic memory impairments caused by temporal lobe epilepsy (TLE) are well documented in the literature. Standard clinical episodic memory tests typically include a 30-min delayed recall test. However, in the past decade, it has become apparent that this standard test does not capture the full range of memory problems in TLE patients. Some patients perform well on a standard 30-min delayed recall test, but show Accelerated Long-term Forgetting (ALF) after 24 h. Although ALF has been investigated in patients with different types of epilepsy, current research on resected TLE patients is missing. In the present study, resected TLE patients were compared to a control group matched on initial learning. They showed normal performance on verbal recall after 30 min, but impairments became apparent after one week. Moreover, the significant interaction between participant group and memory test delay demonstrated that the patients indeed showed an acceleration in forgetting. Furthermore, ALF was present in both left and right resected TLE patients, which contradicts the presence of material-specific hemispheric differences in ALF. In addition, ALF was observed in seizure-free resected TLE patients, thereby demonstrating that this factor is not crucial for long-term memory deficits. The outcome shows that clinicians are likely to underestimate memory deficits in resected TLE patients and, therefore, advocates for the inclusion of ALF tests in standard clinical batteries for both pre- and post-surgery testing sessions.